A microfluidic chamber-based approach to map the shear moduli of vascular cells and other soft materials - Béla Suki (Nature Portfolio, 2017)
Abstract There is growing interest in quantifying vascular cell and tissue stiffness. Most measurement approaches, however, are incapable of assessing stiffness in the presence of physiological flows. We developed a microfluidic approach which allows measurement of shear modulus (G) during flow. The design included a chamber with glass windows allowing imaging with upright or inverted microscopes. Flow was controlled gravitationally to push culture media through the chamber. Fluorescent beads were conjugated to the sample surface and imaged before and during flow. Bead displacements were calculated from images and G was computed as the ratio of imposed shear stress to measured shear strain. Fluid-structure simulations showed that shear stress on the surface did not depend on sample stiffness. Our approach was verified by measuring the moduli of polyacrylamide gels of known stiffness. In human pulmonary microvascular endothelial cells, G was 20.4 ± 12 Pa and decreased by 20% and 22% with increasing shear stress and inhibition of non-muscle myosin II motors, respectively. The G showed a larger intra- than inter-cellular variability and it was mostly determined by the cytosol. Our shear modulus microscopy can thus map the spatial distribution of G of soft materials including gels, cells and tissues while allowing the visualization of microscopic structures such as the cytoskeleleton.